Optimization of bioethanol production from oil palm trunk sap - Norhazimah, Abdul Halim (2016)
Oil palm trunk (OPT) sap was generated from replantation of oil palm. As OPT was generally left at the oil palm plantation for nutrient recycling, research could be conducted to utilize OPT sap as the raw material for bioethanol production. OPT was chopped and pressed through a pressing machine to produce OPT sap, and then the sap was further characterized to determine its suitability as fermentation substrate. The suitability of the OPT sap for bioethanol production was tested by investigating the relationship between temperature and shaking condition towards the fermentation of OPT sap using different microorganisms. At 96 h of fermentation in 30 °C, the highest ethanol yield was obtained by S. cerevisiae Kyokai no.7 in static condition which is 0.485 g/g and 94.92% of sugar conversion to bioethanol. This was followed by mixed culture of S. cerevisiae Kyokai no.7 and Pichia stipitis at 96 h (0.484 g/g and 94.69%). Further investigation on the microorganism kinetic parameter was done. Monod equation and Hinshelwood model were used to relate the specific growth to the concentration of the limiting substrate and simulate bioethanol production rate. Among these three treatments, single S. cerevisiae Kyokai no. 7 microorganism produced the highest ethanol yield of 0.477 g/l.h within the shortest time (12 h). Optimization of bioethanol production from OPT sap was performed using statistical methodology. Selection of the most important factor (10 factors) was done by using Plackett-Burman design (PBD) and it was found that initial pH, peptone and corn steep liquor (CSL) concentration have high influence towards bioethanol yield from OPT sap. Steepest-ascent experimental plan was performed to find suitable curvature of the experimental region. Selected factors were optimized using Box-Behnken design (BBD) at the identified region and it was predicted that the maximum ethanol yield of 0.5406 g/g can be obtained using OPT sap medium consisting of initial pH of 6.50, peptone 6.80 g/l and CSL 13.28 g/l. These conditions were validated experimentally. The predicted result after the optimization was in good agreement with the experimental data. The maximum bioethanol concentration of 0.480-0.500 g/g was obtained experimentally in the optimum condition which was 90.55-93% of the value predicted by Design Expert software. Average bioethanol concentration of 30g/l was obtained in repeated-batch. A kinetic analysis of bioethanol production showed that bioethanol yield and productivity were obtained from optimized OPT sap more stable compared to the corresponding values obtained by using non-optimized condition and by using pure glucose medium. The same condition was validated in 20 liter bioreactor and obtained 0.43-0.45 g/g of ethanol yield. It can be concluded that production of bioethanol from OPT sap as an alternative renewable energy in Malaysia is feasible.